2008
DOI: 10.1016/j.psyneuen.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of the posterior medial bed nucleus of the stria terminalis in modulating hypothalamic–pituitary–adrenocortical axis responsiveness to acute and chronic stress

Abstract: SummaryThe bed nucleus of the stria terminalis (BST) plays a prominent role in brain integration of acute responses to stressful stimuli. This study tests the hypothesis that the BST plays a complementary role in regulation of physiological changes associated with chronic stress exposure. Male SpragueDawley rats received bilateral ibotenate lesions or sham lesions of the posterior medial region of the BST (BSTpm), an area known to be involved in inhibition of HPA axis responses to acute stress. Chronic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 51 publications
7
66
2
4
Order By: Relevance
“…Most notably, the influence of noradrenergic neurotransmission in the BNST on HPA activity should be considered (Cecchi et al, 2002a;Morilak et al, 2005). The BNST, through its different anatomical subnuclei, depending on the type and duration of stress exposure, plays a key role in HPA axis activity, inhibiting or stimulating it (Choi et al, 2007(Choi et al, , 2008. The stressinduced release of noradrenaline into the BNST seems to activate the neural circuits involved in HPA axis activation, with the participation of local a 1 adrenoceptors (Cecchi et al, 2002a(Cecchi et al, , 2002bPardon et al, 2003;Morilak et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, the influence of noradrenergic neurotransmission in the BNST on HPA activity should be considered (Cecchi et al, 2002a;Morilak et al, 2005). The BNST, through its different anatomical subnuclei, depending on the type and duration of stress exposure, plays a key role in HPA axis activity, inhibiting or stimulating it (Choi et al, 2007(Choi et al, , 2008. The stressinduced release of noradrenaline into the BNST seems to activate the neural circuits involved in HPA axis activation, with the participation of local a 1 adrenoceptors (Cecchi et al, 2002a(Cecchi et al, , 2002bPardon et al, 2003;Morilak et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the BNST is activated by different stressful stimuli (Greenwood et al, 2005;Beijamini and Guimaraes, 2006;Muigg et al, 2007) and plays an important role in the regulation of the activity of the hypothalamicpituitary-adrenal (HPA) axis in response to stress (Forray and Gysling, 2004;Choi et al, 2007Choi et al, , 2008. Moreover, exposure to inescapable stress elicits structural changes in the BNST (Pego et al, 2008), as well as in the amygdala (Roozendaal et al, 2009), hippocampus (Rodrigues et al, 2009), and medial prefrontal cortex (Izquierdo et al, 2006), often accompanied by increased anxiety-like and depressive-like behaviors in rodents (Cryan et al, 2002;Izquierdo et al, 2006;Rodrigues et al, 2009;De Paula Soares et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The BSTp and MeA are involved in the processing of pheromonal input in other rodents and have associated roles in controlling neuroendocrine function and sexual behavior [Simerly, 2002]. The BSTp has also been implicated in the regulation of stress responses in other rodents via its projections to the PVN [Choi et al, 2008]. While the relationship between stress and social status in naked mole-rats is not simple Faulkes, 1997, 1998], it seems likely that at least some components of the hypothalamic-pituitaryadrenal axis are affected when an animal becomes a breeder.…”
Section: Discussionmentioning
confidence: 99%
“…The CRH neurons of the PVN receive inhibitory GABAergic projections from the bed nucleus of the stria terminalis (BNST) which relays information from the PFC (234) as well as the hippocampus (235). Studies using lesions of subnuclei of the BNST in rats demonstrate a posteriormedial region of the BNST acts as the relay from limbic structures to PVN (36,37). Lesions of the lateral fornix have shown that the ventral subiculum of the hippocampus projects to the PVN and results in increased CRH and AVP expression in the medial parvocellular PVN, and affect stress responsiveness of the HPA axis (23,46,116,233,235,253), suggesting a tonic suppression of PVN-releasing hormones by corticosteroid action in hippocampus.…”
Section: Sites and Mechanisms For Rapid Inhibitory Effects Of Corticomentioning
confidence: 99%